AI-Driven Omnichannel Marketing and Customer Experience : A Bibliometric Overview - Brindha, G.; Vidya, M.; Reshma, M. (Indian Journal of Marketing, 2025)
Purpose : The study examined the significance of omnichannel marketing in light of the rapid technological growth accentuated by artificial intelligence (AI) and its consequent effect on consumer awareness. To attain this, the study utilized scientometric methods to shed light on the available research on the topic, while highlighting its growth over the years and the future trends in the area. Methodology : This research employed bibliometric analysis of literature on omnichannel marketing and AI through the Scopus database using VOSviewer. The authors collected and analyzed research works using the keywords: omnichannel, artificial intelligence, and customer experience, belonging to the period from 2014 to 2024. Findings : Five distinct thematic clusters with 45 keyword items related to consumer behavior were identified in the study. The findings encouraged marketers to identify demanding domains of new age technologies, which would assist them in integrating all their channels to offer a unified experience for different customer profiles. Practical Implications : The results of this study provided a technology-based action plan for businesses to rebuild their image as customer-focused by providing tailored customer experiences. It also predicted the rapid changes in customer expectations across generations, reiterating the need for businesses to evolve quickly with the aid of new technologies. Originality : Unlike previous studies on omnichannel marketing, the current research offered a consolidated overview of omnichannel marketing, customer experience, and AI through a bibliometric lens. It contributed to theory by expanding the scope of technology adoption and customer experience frameworks.